PENGARUH PENGETAHUAN ANGGOTA DEWAN TENTANG ANGGARAN, POLITICAL BACKGROUND TERHADAP PENGAWASAN KEUANGAN DAERAH (APBD) DENGAN PARTISIPASI MASYARAKAT DAN TRANSPARANSI KEBIJAKAN PUBLIK SEBAGAI VARIABEL MODERATING (Studi Empiris DPRD Kota se Provinsi Sumatera Barat) - Maisyarah, Maisyarah; Emrinaldi, Emrinaldi; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to know about (1) the influence of board member's knowledge about budget to financial supervision daearah (APBD) (2) Influence of political background to financial supervision daearah (APBD) (3) Influence of community participation can moderate relationship between board member's knowledge about budget with local financial oversight (APBD). (4) The effect of public policy transparency may moderate the relationship between board council members' knowledge of budgets and the supervision of Regional Finance (APBD). This research uses purposive sampling method to get the sample for this research. . The population in this study is all member of DPRD cities in West Sumatra, the cities is Payakumbuh, Bukittinggi, Padang Panjang, Pariaman, Padang, Solok, and Sawahlunto. The sample used is 50 respondents. The technique of data gathering is by spreading the questionnaire. For analysis the hypothesis of these variable is using SmartPLS. The results show that (1) the relationship of Board Member’s Knowledge about the budget, with the supervision of local finance (APBD) in statistical value 4,790 and 2,580 (2) community participation is able to moderate the relationship between the board members' knowledge of the budget and the regional financial contro in statistical value 4,015 (3) transparency can not moderate the knowledge relation in statistical value 1,481 (4) political background has a negative relationship to local financial control (APBD) in statistical value 6,574 and 3,032.Keywords : Board Member’s Knowledge About Budget, Political Background, Regional Financial Supervision (APBD) , Participation Of Community, Public Policy Transparency